2014
DOI: 10.5114/ceji.2014.47736
|View full text |Cite
|
Sign up to set email alerts
|

Clinical immunology Gene expression disorders of innate antibacterial signaling pathway in pancreatic cancer patients: implications for leukocyte dysfunction and tumor progression

Abstract: The study was carried out to investigate changes in gene expression of innate antibacterial signaling pathways in patients with pancreatic cancer. Expression of the following genes was measured in peripheral blood leukocytes of 55 patients with pancreatic adenocarcinoma using real-time polymerase chain reaction (RT-PCR): TLR4, NOD1, MyD88, TRAF6 and HMGB1. The levels of expression of TLR4, NOD1 and TRAF6 genes were significantly elevated (p = 0.007; p = 0.001 and p = 0.01, respectively), while MyD88 expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 85 publications
0
7
0
Order By: Relevance
“…These patients were treated previously in other surgical wards and had organ damage after major abdominal surgeries, reoperations, including a fairly homogeneous group of patients with septic infections of the catheter for parenteral nutrition at home or a group of patients with severe acute pancreatitis. The current genetic tests were performed at the mRNA level and were preceded by the analysis of changes in the expression of the same genes during treatment (days 1, 3, 7) and in other groups of patients in order to reduce the impact of other factors on the tested parameters, as it happened many times during our previous studies on inflammatory response mediators [ 82 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients were treated previously in other surgical wards and had organ damage after major abdominal surgeries, reoperations, including a fairly homogeneous group of patients with septic infections of the catheter for parenteral nutrition at home or a group of patients with severe acute pancreatitis. The current genetic tests were performed at the mRNA level and were preceded by the analysis of changes in the expression of the same genes during treatment (days 1, 3, 7) and in other groups of patients in order to reduce the impact of other factors on the tested parameters, as it happened many times during our previous studies on inflammatory response mediators [ 82 , 89 ].…”
Section: Discussionmentioning
confidence: 99%
“…The objective of this study was an attempt to determine whether the expression of genes involved in innate antibacterial response (TLR2, NOD1, TRAF6, HMGB1 and Hsp70) in peripheral blood leukocytes in critically ill patients, may undergo significant changes depending on the severity of the infection and the degree of malnutrition. The selection of genetic parameters studied was based on the results of our previous studies conducted in malnourished patients [ 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…Stimulation of NOD1 and NOD2 was found to be protective in inflammation-induced CRC, [69][70][71]80 whereas there was no straightforward answer as to whether activation of NOD1 in the stomach promotes or prevents the development of GC. [72][73][74] Moreover, NOD1 was found to be upregulated in PC, 79 HNSCC, 77,78 OSCC, 76 and GC, 73,74 as opposed to certain studies that reported NOD1 downregulation in the cases of OSCC 75 and GC. 72 NOD2 was also found to be upregulated in GCs.…”
Section: The Role Of Nod Proteins In Cancer Developmentmentioning
confidence: 99%
“…In an orthotopic xenograft model of SCID mice, a combination of proteasome inhibitor (MG132) and ionizing radiation therapy resulted in a significant increase in the tumor growth delay and a decreased tumor tissue expression of TRAF6 [149]. Additionally, we have recently proposed that overexpression of TLR4, NOD1 and TRAF6 genes and lower MyD88 gene expression in peripheral blood leukocytes of patients with pancreatic cancer, could contribute to chronic inflammation and tumor progression by the up-regulation of the innate antibacterial response (e.g., to LPS) [150]. Although the evidence suggesting carcinogenic and therapeutic effects of stimulation or inhibition of TLRs is increasingly growing, it still remains unclear what kind of changes in gene expression of the TLR signaling pathways in leukocytes are associated with pancreatic cancer.…”
Section: Innate Antibacterial Signalingmentioning
confidence: 99%